Fūziju rezervju saistība ar autostereogrammu atpazīšanu - Liepa, Iveta (Latvijas Universitāte, 2009)
Bakalaura darbs ir uzrakstīts latviešu valodā datorsalikumā uz 57 lapām, satur 22 attēlus, 7 tabulas, 3 pielikumus un 23 atsauces uz literatūras avotiem. Atslēgas vārdi:autostereogrammas, fūziju rezerves, stereoredze. Mērķis:izpētīt fūziju rezervju saistību ar autostereogrammu ieraudzīšanu. Metode: eskperimentā tika izmantotas piecas dažādu veidu autostereogrammas. Eksperimenta laikā apmācāmajai grupai (grupa, kas pirms eksperimenta autostereogrammas neredzēja) mēģināja iemācīt saskatīt autostereogrammas un salīdzināt viņu izvēlētās skatīšanās metodes ar zinošās grupas skatīšanās metodēm (grupa, kas autostereogrammas redzēja arī pirms eksperimenta). Abu grupu starpā tika salīdzinātas arī fūziju rezerves un stereoredzes asums. Rezultāti:fūziju rezerves starp abām grupām nebija statistiski atšķirīgas. Lielākā daļa dalībnieku autostereogrammu saskatīšanai pielietoja "krustoto skatīšanāš" tehniku. Abu grupu stereoredzes asuma vērtības nebija statistiski atšķirīgas. Secinājumi:1.„Krustotā skatīšanās” tehnika ir vispiemērotākā tam, lai iemācītu saskatīt un atpazīt autostereogrammas.2. Fūziju rezerves nav saistītas ar to vai cilvēks pirms eksperimenta varēja vai nevarēja saskatīt autostereogrammas. 3.Stereoredzes asums abām eksperimenta grupām nav statistiski atšķirīgs. 4.Gan zinošajai, gan apmācāmajai grupai vislielākās saskatīšanas grūtības bija tieši ar autostereogrammu, kurai virsū uzlikts cits zīmējums ieraudzīšanu.

The bachelor paper is written in Latvian and contains 57 pages. It comprises 22 illustrations, 7 tables, 3 appendices. 23 sources are referred to in this bachelor paper. Key words: autostereograms, fusional reserves, stereovision. Purpose: To investigate the connection between fusional reserves and the ability of seeing autostereograms. Methods: In the course of the experiment the participants were dividend into two groups. The first group was the ‘tutored’ group - the participants of which were not shown autostereograms before the experiment. The second group was the ‘knowing’ group – the participants of this group were shown autostereograms before the experiment. During the experiment all the participants were demonstrated five different autostereograms. One of the major objectives was to compare the viewing methods used by the ‘tutored’ group and the methods used by the ‘knowing’ group. Both groups of participants got their fusional reserves measured and the acuity of stereovision determined. Results: Comparing the values of fusional reserves of both groups, they can be considered as statistically equal. 80% of the members of the ‘tutored’ group applied the ‘crossed’ viewing method in order to sight the autostereograms. Similarly, the majority of the ‘knowing’ group members (70%) applied the ‘crossed’ viewing method to sight the autostereograms. Comparing the acuity of stereovision of both groups, they were not statistically different. Conclusions:1. The ‘crossed’ viewing method is the most suitable method for teaching to see and recognize autosterograms. 2. The fusional reserves are not connected with whether the participant was or was not able to sight autostereograms before the experiment. 3. The acuity of stereovision of both groups does not differ statistically. 4. For both the ‘tutored’ and the ‘knowing’ group the autostereogram which was partly covered by another picture was the most problematic one to see.
Relationship between fusional reserves and autostereograms recognition
Keywords: Fizika